Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1515/1556-3758.2023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process conditions and carrier concentration for improving drying yield and other quality attributes of spray dried black mulberry (Morus nigra) juice

Abstract: The objective of this work was to study the influence of spray drying conditions on the physicochemical properties of black mulberry (Morus nigra) powder. A lab-scale spray dryer was employed for the spray drying process and maltodextrin DE=9was used as carrier agent.Response surface methodology (RSM) was performed to examine the effects of independent variables on the drying yield, color change, and total anthocyanin content and to determine the optimum processing conditions. Independent variables were: inlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 0 publications
4
20
1
3
Order By: Relevance
“…Similar findings were reported by Fazaeli, Emam‐Djomeh, Kalbasi‐Ashtari, and Omid (2012a in the spray drying of black mulberry juice, where increasing the concentration of maltodextrin causes lightness ( L* value) to increase but a* and b* values to decrease. Fazaeli et al (2012a) also revealed that maltodextrin concentration could affect the rate of browning reactions if spray drying is performed at an elevated temperature. They found the browning index of black mulberry powders were significantly increased when the inlet air temperature rose.…”
Section: Resultssupporting
confidence: 88%
“…Similar findings were reported by Fazaeli, Emam‐Djomeh, Kalbasi‐Ashtari, and Omid (2012a in the spray drying of black mulberry juice, where increasing the concentration of maltodextrin causes lightness ( L* value) to increase but a* and b* values to decrease. Fazaeli et al (2012a) also revealed that maltodextrin concentration could affect the rate of browning reactions if spray drying is performed at an elevated temperature. They found the browning index of black mulberry powders were significantly increased when the inlet air temperature rose.…”
Section: Resultssupporting
confidence: 88%
“…Largo Avila et al () explained this phenomenon by the fusion of existing carbohydrates in sugar‐rich materials. On the other hand, there are also several reports of a positive relationship between inlet/outlet air temperature and product yield (Fazaeli, Emam‐Djomeh, Kalbasi‐Ashtari, & Omid, ; Vardin & Yasar, ). These authors suggested that this may be explained by a more efficient heat and mass transfer, which occurs at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Dehydration is one of the most common techniques used to preserve food. In addition, it also entails a reduction in the volume and weight of the product, which facilitates its transport and handling [11].…”
Section: Introductionmentioning
confidence: 99%